Effect of COVID-19 Frontline Nurses’ Profession Perception on Their Intention to Stay: The Mediating Role of Job Satisfaction - Ahram Im MSN, RN; Chin Kang Koh PhD, AGCNS-BC, RN (SAGE Open Nursing, 2023)
Introduction Understanding the factors affecting the intention of frontline nurses during the coronavirus disease (COVID-19) pandemic to stay in the nursing profession is essential for developing strategies to overcome the challenges associated with the pandemic. Objectives This study aimed to examine the mediating effect of nurses’ job satisfaction on the relationship between their sense of calling, job-esteem, and the intention to stay in their profession. Methods The study used a previously collected dataset, sourced from a dedicated COVID-19 hospital in Seoul City, South Korea. Original data were collected from June to July 2021. The study sample consisted of 134 nurses who provided direct care to patients. The intention to stay was measured with the following question: “Are you willing to work during this COVID-19 pandemic?”. The Job Satisfaction Scale from the Korean Labor and Income Panel Study, Korean version of a Multidimensional Calling Measure, and Job-Esteem Scale for Hospital Nurses were utilized. Associations between the study variables were estimated using bivariate correlation analyses and bootstrapping mediation analyses. Results In the bivariate correlation analysis, nurses’ sense of calling ( r  = .36, p  < .001), job-esteem ( r  = .32, p  < .001), and job satisfaction ( r  = .39, p  < .001) were significantly associated with the intention to stay. In the mediation analysis, job satisfaction partially mediated the relationship between the sense of calling and the intention to stay (total effect; B  = 0.410, p  < .001) and fully mediated the relationship between job-esteem and the intention to stay (total effect; B  = 0.549, p  < .001). Conclusion Enhancing nurses’ job satisfaction is crucial for fostering the retention of the nursing workforce amid the pandemic. Consequently, it is imperative to closely examine the job satisfaction and work environment of frontline nurses to identify areas in need of improvement. Addressing the factors that impede nurses’ job satisfaction is essential to unlock the positive effects of a sense of calling and job-esteem.